STUDI DAMPAK PERKEMBANGAN PEMBENIHAN IKAN LAUT TERHADAP PENURUNAN KUALITAS LINGKUNGAN DI KECAMATAN GEROKGAK KABUPATEN BULELENG - Suko Ismi; I Wayan Arthana; I W. Budiarsa Suyasa (Master Program of Environmental Science, Postgraduate Program of Udayana University)
The purpose of this research is to investigate influence of marine fish hatchery to degradation environmentalquality in Gerokgak District, measurement was done through physical, chemical and microbiologycal analysis.Thesample was taken from 17 stations well water, and 8 stations sea water with 2 stations coming from water discard marinefish hatchery of Gondol Orchard. Data analysis of wells water to campare with water quality standart category I and seawater comparing with the live for animal sea water according to Regulation of The Governor Bali No. 8 Year 2007. Seawater pollutan level was counted through index of diversity and integrated score, to know the resemblance physical andchemical caracteristic among station was analysis by cluster.Result of the research indicates that some parameters of wells water have passed standart water quality namely :Salinity, BOD5, nitrit, phospat, iron , mangan, copper, zink, cobalt, cadmium, dan bacteria coliform feces content. Clusteranalysis wells water if we classify into 3 groups namely first group station 2, 4, 5, 8 until 17, the location of wells 2, 4 and5 near for hatcheries but have resemblance caracteristic with wells far for hatcheries that is station 8-17. Second groupstation 3, 6 and 7 have location near hatcheries and third group station 1 only near hatcheries location. Nearness betweenstation on one group caused resemblace caracteristic, although different wells distance. Parameters sea water have passedstandart water quality namely : nitrat and phospat. Can be found 21 genus plankton from 6 phylum with composition 61%Bacillariophyta, 5% Cyanophyta, 10% Protozoa, 5% Ctenophora, 14% Arthropoda. Index diversity (H’) 0.078 – 1.968 itindicates about medium to high pollution, index uniformities (E) 0,033 – 0,473 its means that uniformities low tomedium, index domination (C) 0,167 – 0,974 it’s meaning have domination partial of plankton a low until high. Integrated score rate have value 4,63 – 6,25 the meaning is water have a medium until heavy of pollution. Cluster analysissea water if it is classified into 3 groups namely first group that is station 1 until 5 that in coastal area with direct watercoming from discard water marine fish hatchery different caracteritic with second group station 6,7 and 8 this area farfrom the beach, next third group B1 and B2 this station water discard from marine fish hatchery.